2022
DOI: 10.7759/cureus.22031
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Probiotics in Management of Celiac Disease

Abstract: The objective of this study was to interpret any rule of probiotics in the management of celiac disease and apply the results to improve the quality of life of patients with celiac disease if the result comes in favor of probiotics. Materials and methodsIt was a cross-sectional study conducted in the gastroenterology unit of Nishtar Medical University, Multan. A total of 170 children with celiac disease were enrolled in the study and divided into two groups (A and B) using a computer-generated table of random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 31 publications
1
9
0
4
Order By: Relevance
“…lactis Bi1, Bifidobacterium breve Bbr8, and B. breve Bl10) was effective in improving the severity of IBS-type symptoms in CD patients on a strict GFD [ 48 ]. Similar results were reported in the pediatric population by Basit Ali et al Probiotics were found to be highly efficient in terms of reduction in diarrhea in CD and are useful tools to be considered in improving the quality of life among young patients with CD [ 49 ]. However, the data reported are contradictory.…”
Section: Less Aging More Healing: Is There a Role For Probiotics And ...supporting
confidence: 79%
“…lactis Bi1, Bifidobacterium breve Bbr8, and B. breve Bl10) was effective in improving the severity of IBS-type symptoms in CD patients on a strict GFD [ 48 ]. Similar results were reported in the pediatric population by Basit Ali et al Probiotics were found to be highly efficient in terms of reduction in diarrhea in CD and are useful tools to be considered in improving the quality of life among young patients with CD [ 49 ]. However, the data reported are contradictory.…”
Section: Less Aging More Healing: Is There a Role For Probiotics And ...supporting
confidence: 79%
“…No signi cant difference was reported regarding diarrhoea, constipation, abdominal pain, and vomiting after treatment. Ali et al [24] reported a signi cant higher reduction in stool frequency in probiotic arm compared to placebo after four-weeks of treatment. [17,23].…”
Section: Gastrointestinal Symptomsmentioning
confidence: 99%
“…1). Fourteen studies [6,[15][16][17][18][19][20][21][22][23][24][25][26][27] were included in qualitative analysis and ve [19,25,15,6,17] in quantitative analysis.…”
Section: Study Search Overviewmentioning
confidence: 99%
“…Table 2 presents the characteristics of the included studies. Clinical trials were carried out in Argentina [16,20,21], Australia [15], Brazil [22], Italy [6], Pakistan [24], Slovenia [18, 19,23], Spain [17], Sweden [25,26], and Turkey [27]. Altogether, 871 participants were included in this systematic review, of whom 203 were CDA cases.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation